Congruencia de la actividad investigativa y el perfil de los investigadores universitarios de la Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” con las necesidades empresariales del entorno socioeconómico - Espinoza Loor, Oscar Leonidas (2020)
The objective of this project was to study the case study on the research activity of the teachers of Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López” to determine the level of consistency with the needs of the socioeconomic environment. The methodology applied was interviews with key people from the university who provided information on the agreements they have with companies in the area, in addition, a survey was applied to the teachers of ESPAM MFL, the relevant results indicated that 44% of the projects are not related to the socioeconomic environment, and 51% indicated that they do not have sufficient resources to execute all the projects. On the other hand, interviews were conducted with company representatives, who stated that it is necessary and important to increase the transfer of knowledge and the execution of agreements with companies close to the university sector. From the data, in addition, it was concluded that there is a low level of consistency in various projects, and one of the main causes is that the profile of the research teachers is not related to the research activities they are carrying out, which limits to generate innovations or solutions efficiently for the needs of the socioeconomic environment.